1983
DOI: 10.1002/mde.4090040105
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sources of technology: An analysis of induced innovations

Abstract: This paper considers why firms differ in the degree to which they rely on their internal R&D organization for generating new technologies (induced innovations) rather than on existing external technology markets (purchased innovations). An empirical model is suggested to explan inter-firm differences in the percentage of new technology induced through R&D efforts. The analysis suggests that such differences are systematically related to the firm's size, its competative environment, and its degree of diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Further literature can be found in Wang and Kafouros (2009), Blalock and Gertler (2004), Falvey, Foster and Greenaway (2004), Kafouros and Buckley (2008), MacGarvie (2006), Link (1983), Danell and Persson (2003), Castellacci and Natera (2013) and Monreal- Pérez et al (2012).…”
mentioning
confidence: 99%
“…Further literature can be found in Wang and Kafouros (2009), Blalock and Gertler (2004), Falvey, Foster and Greenaway (2004), Kafouros and Buckley (2008), MacGarvie (2006), Link (1983), Danell and Persson (2003), Castellacci and Natera (2013) and Monreal- Pérez et al (2012).…”
mentioning
confidence: 99%
“…Not all R&D is productive, and increased R&D does not necessarily translate to increased innovations (Link, 1983;Bebchuk and Stole, 1993). Although studies have shown a positive relationship between stock concentration and R&D investments for US firms (i.e.…”
Section: Theoretical Background the Link Between Ownership And Innovamentioning
confidence: 99%
“…Arora (1996) suggests that transactions costs can be advantageous to the owner provided that knowledge transfer is bundled with engineering and training. Link (1983) studies the proportion of technological advance that is internal to the firm. He finds that firm size and diversification increase the internal proportion.…”
Section: B the Limits Of The Firm In Randdmentioning
confidence: 99%